(3GdWHbGJ GdcHjQs - (3eMeO Hf SYO Hf efjY GdRgQj, CHh YHO Gddg cGJH GdhGbOj, GHf SYO , J (B230 (3g` s
(3ChdgG (B:s
(3GdWHbI GdNGeSI YHO Gddg Hf GdYHGSI Hf YHO GdeWdH s
(3BNQgG (B:s
(3JQLeI (B" (3cKjQ Hf GdSGFH (B" (3hBNQ eG ajg (B" (3BNQ GdWHbI GdNGeSI (B" (3hgj BNQ WHbGJ CUMGH QShd Gddg Udi Gddg Ydjg hSde jJdhg WHbGJ GdJGHYjf s
(3GdfSNI LRA ef GdeNWhW hdjS cdgs
(3HBNQgG SeGY SfI (B599 (3hGdfSNI ebGHdI Ydi CUhd LjOI PcQJ ai BNQ GdfSNIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B136 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B21s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeMehOjI (B- (3HecJHI GdeOjfI GdefhQI GdYGeI(B((3JGQjN (B33) s
Keywords: (3GdJGQjNs